Три женщины в городском пейзаже - Метлицкая Мария (Женские судьбы. Уютная проза Марии Метлицкой, 2021)
Экземпляры: ЦБ/6/31 (20210617) / Инвентарный номер: 61122 / Цена: 300.00 / Сис.шифр: Р2 / Авт.знак: М 54 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6